Pengaruh Current Ratio, Deb to Equty Ratio, Profitability dan Total Assets Turnover terhadap Nilai Perusahaan: (Studi Empiris pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Cristina Lasmaria Gultom; Desy Anggraeni (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of current ratio, debt to equity ratio, profitability, and total assets turnover on the value of pharmacy subsector companies listed on the Indonesia Stock Exchange for the period 2019-2023. The data used in this research is secondary data in the form of financial reports of pharmacy subsector companies listed on the Indonesia Stock Exchange for the period 2019-2023. There were 13 (Thirteen) companies as population for this study. Where sampling was carried out using a purposive sampling technique, with the total sample obtained according to the criteria amounting to 10 (Ten) companies. The analytical method used is multiple linear regression analysis and tested using the Statistical Package for the Social Science (SPSS) version 25 program. The research results show that the variables debt to equity ratio, and profitability have a significant effect on company value. Meanwhile, current ratio and total asset turnover does not have a significant influence on company value.